2018
DOI: 10.1017/s1041610218001606
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the prevalence and associations of stress and burnout among staff in long-term care facilities for people with dementia

Abstract: Background:Care home staff stress and burnout may be related to high turnover and associated with poorer quality care. We systematically reviewed and meta-analyzed studies reporting stress and burnout and associated factors in staff for people living with dementia in long-term care.Methods:We searched MEDLINE, PsycINFO, Web of Science databases, and CINAHL database from January 2009 to August 2017. Two raters independently rated study validity using standardized criteria. We meta-analyzed burnout scores across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 43 publications
4
96
2
3
Order By: Relevance
“…Research on nursing home staff burnout has also mostly come from abroad without particular focus on licensed nurses . While one expects that similar factors contribute to burnout and missed care for nursing assistants, licensed practical nurses (LPNs), and RNs in nursing homes, the latter have unique clinical leadership roles that warrant examining them separately.…”
mentioning
confidence: 99%
“…Research on nursing home staff burnout has also mostly come from abroad without particular focus on licensed nurses . While one expects that similar factors contribute to burnout and missed care for nursing assistants, licensed practical nurses (LPNs), and RNs in nursing homes, the latter have unique clinical leadership roles that warrant examining them separately.…”
mentioning
confidence: 99%
“…Similarly, although all staff attended training, the staff recruited to the study reported high levels of selfassessed competence at baseline and had higher personal accomplishment and lower depersonalisation scores on the burnout scale than did care home staff in general. 42 We planned to analyse cost-effectiveness, which is important in the UK because it informs the National Institute for Health and Care Excellence (NICE) guidelines. The fact that the cost of MARQUE was not found to be significantly less than TAU might be explained by the fact that cost data has higher variance than effect data and the study was powered for the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, another study that measured the association between age and burnout found no significant association. 45 Therefore, more research is needed to identify the relationship between these variables and burnout in professional caregivers of persons with dementia.…”
Section: Discussionmentioning
confidence: 99%